Sustainability Report Disclosure and Firm Value: The Mediating Role of Corporate Reputation - Rijal Habibulloh (P3M Politeknik Negeri Bengkalis, 2026)
This research analyzes and proves the effect of sustainability report disclosure on firm value,measured based on overall disclosure and economic, environmental, and social performanceaspects. It also examines the mediating role of corporate reputation in this relationship. Thestudy focuses on companies listed in the IDX ESG Leaders from 2020 to 2023, using a purposive sampling technique and obtaining 14 companies with 56 units of analysis. Sustainability report disclosure is measured using the GRI standard, which contains three mainaspects: economic, environmental, and social performance. Firm value is measured by Price toBook Value (PBV), and corporate reputation is proxied by the number of awards received. Thedata used are secondary data in the form of annual reports and sustainability reports, which areanalyzed using a quantitative approach with the panel data path analysis method. The resultsshow that sustainability report disclosure, whether measured as a whole or based on aspects ofeconomic, environmental, and social performance, has no significant effect on firm value. Inaddition, corporate reputation also cannot mediate the relationship between sustainabilityreport disclosure and firm value. These findings indicate that although the sustainability reporthas been disclosed, it has not been able to be a significant factor in increasing firm value. Thisstudy provides insight into the fact that sustainability disclosure requires a more integratedstrategy to have a real impact on firm value.